Profiles of illness and injury among South African elite athletes with disability at the 2012 Summer Paralympic Games - Constantinou, Demitri (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Epidemiological data is important to better understand injury and illness patterns in para athletes. Medical teams used a web-based injury and illness surveillance system (WEB-IISS system) to all the para-athlete injuries and illnesses during the 2012 London Paralympic games. All team physicians could access the system at any time to log data, providing a vast database for potential research. The relative ease of data collection permits large amounts of data to be analysed, providing important surveillance data on injury and illness. Data on the South African para-athletes, provided by the team's Chief Medical Officer, were assessed and compared to all countries. This study aimed to describe the illness and injury profiles in South African elite paraathletes who participated in the 2012 Summer Paralympic Games; and compare these profiles to data from the other countries that participated. A retrospective sub-analysis of the data-set collected from a large prospective study of injury and illness at the London Summer Paralympic Games in 2012 was compared to data collected on all para-athletes from input by team physicians into the WEB-ISS system. In total, 62 South African para-athletes presented with 19 injuries, with an injury rate of 21.9 per 1000 athlete days. Twenty-five para-athletes presented illness, with an illness rate of 28.8 per 1000 athlete days. The overall injury and illness rate in the South African para-athletes was higher than the injury and illness rate in all para-athlete participants at the London Paralympic Games. The anatomical distribution of injuries (lower limbs, axial and upper limbs) and the nature of illness (respiratory, skin & subcutaneous and digestive systems) were however similar. Causative factors are not evident and need to be further studied. Increased efforts in injury and illness surveillance and preventative programmes should be employed to reduce the incidence of injury and illness, and their severity . Such efforts in para-athlete care should be ongoing with surveillance to monitor and manage trends to ensure the culmination of Paralympic competition does not result in high rates of injury and illness. Education of healthcare providers, para-athletes, coaches and others in the management of para-athletes, is key.